KINERJA DAN PROSPEK PENGEMBANGAN BAHAN BAKAR NABATI DI INDONESIA (Forum Penelitian Agro Ekonomi, 2016)
Development of bio-fuel energy in Indonesia deals with serious challenges. This study aims to analyze performance and development prospects of bio-fuel energy based on production performance, agribusiness, and financial feasibility of industries using coconut palm, jatropha, cassava and sugarcane as raw materials for producing of bio-fuel. It is found that bio-fuel production is influenced by land area size. All crops are feasible to develop, except jatropha than has lower bio-fuel content below the standard. Financial feasibility study shows that biodiesel and bio-ethanol industries reasonable to develop. The policy suggested is land conversion control, expanding planting areas by utilizing marginal land, price incentive and agribusiness improvement, research and development, farmers’ access to capital, farmers’ partnerships with businessmen, restructuring the bio-diesel processing, and standardization.